Envelhecimento ativo: um desafio para a equipe multidisciplinar e para as pessoas idosas frequentadoras da Unidade de Atenção ao Idoso (UAI), no município de Uberaba - MG - Pedrosa, Wanderley Cesar [UNESP] (2014)
The present work aims the ageing process from local-to-global. This process is a still challenge for society as a whole and cannot afford to wriggle out of, that is inherent to all human being, regardless of nationality, ethnicity, color, gender, religion. A Unidade de Atenção ao Idoso (UAI),( The Central for Support Older People), has become a fertile field of this research whose purpose is analyze the active aging process, with a multidisciplinary team perspectives and for elderly people to attend UAI in Uberaba city, MG. The specific objectives were realized through historicity of municipal government policy to the elderly assistance study in Uberaba city, from 1995 to 2012, and the important role that the people had played at the UAI permanent assistance policy process; to describe the socio-economic background to attend UAI, understanding the multidisciplinary team work and the elderlies in relation to the active aging, as well as the factors which led you take apart of the several projects offered by institution, to analyze the impact trigged in elderlies daily life, after their participation on UAI activities, as well as the important role that this institution takes in their daily life and the multidisciplinary team work. This work is an exploratory and qualitative research. It has been used a questionnaire as a part of the data collection process and it has selected fifteen projects among sixty elderlies groups, between the age of 60 and 100, who participated in four projects by week and has entered into the institution until 2010, together with the multidisciplinary team. The diagnosis of CT data has focused on dialectical materialism and the during this process way was based on content analysis by Bardin (1977), that enable the comprehension of the multiple meanings going beyond the words of each person interviewed. On the basis of interviews and analysis of data collected, understanding how it works as well as the relative...